PENGARUH PERADABAN ISLAM TERHADAP DUNIA BARAT - Huzain, Muh. (P3M STAIN Sorong, 2018)
The emergence of Islam influenced the revolution and made a wave of culture toward a new world when experiencing an era of darkness. The progress of Greek civilization in the West could not be continued by the Roman empire and Roman domination in the classical era until the middle ages; which was then the rise of the West in the era of renaissance in the 14-16th century. This paper will reveal the influence of Islam on the development of the Western world, since the emergence of contact between Islam with the West in the Classical era until the middle ages. There are different opinions among historians about who and when the first contact between Islam and the West took place. The first contact, however, occurred when the areas of East Roman government (Byzantium), Syria (638) and Egypt (640) fell into the hands of the Islamic government during the reign of Caliph Umar bin KhaÅ£Å£Äb. The Second contact, at the beginning of the eighth and ninth centuries occurred when the kings of Islam were able to rule Spain (711-1472), Portugal (716-1147), and important Mediterranean islands such as Sardinia (740-1050), Cicilia (827-1091), Malta (870-1090) as well as several small areas in Southern Italy and French Southern France. The third contact, took place in Eastern Europe from the fourteenth to early twentieth century when the Ottoman empire ruled the Balkan peninsula (Eastern Europe) andÂ Southern Russia. The Ottoman empires powers in Europe covered YunÄni, Bulgaria, Albania, Romania, Yugoslavia, Hungary, parts of Rhode, Cyprus, Austria and parts of Russia. Of the three periods of contact, the greatest influence was in the second contact period, where the decline of Western science in the dark era, while in the Islamic world developed advanced and produces scientists, thinkers and intellectuals in various sciences. This influence can be seen from the sending of students studying to the university of Islamic area, the establishment of the university, the translation and copying of various scientific literature such as natural science (Science of astronomy, Mathematics, Chemistry, Pharmacy, medicine, architecture etc) and Social Science history, philosophy, politics, economics, earth sciences, sociology, law, culture, language, literature, art, etc.). The Historians recognize that the influence of Islamic civilization is very great on the development of the West, which culminated in the renaissance or rise of Western civilization in Europe after the dark era.